2021
DOI: 10.1101/2021.11.10.468053
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An Infant Sleep Electroencephalographic Marker of Thalamocortical Connectivity Predicts Behavioral Outcome in Late Infancy

Abstract: Infancy represents a critical period during which thalamocortical brain connections develop and mature. Deviations in the maturation of thalamocortical connectivity are linked to neurodevelopmental disorders. There is a lack of early biomarkers to detect and localize neuromaturational deviations, which can be overcome with mapping through high-density electroencephalography (hdEEG) assessed in sleep. Specifically, slow waves and spindles in non-rapid eye movement (NREM) sleep are generated by the thalamocortic… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…This may explain differences in the functional as well as the clinical relevance of these oscillations which have repeatedly been reported. For example, sleep spindle density has been identified as a predictor of behavioral outcomes in infancy, whereas slow wave activity showed no such effect 73 . Furthermore, increases in sleep EEG coherence in children with childhood onset schizophrenia as compared to healthy controls were more prominent in the delta than in the sigma band 74 , 75 .…”
Section: Discussionmentioning
confidence: 99%
“…This may explain differences in the functional as well as the clinical relevance of these oscillations which have repeatedly been reported. For example, sleep spindle density has been identified as a predictor of behavioral outcomes in infancy, whereas slow wave activity showed no such effect 73 . Furthermore, increases in sleep EEG coherence in children with childhood onset schizophrenia as compared to healthy controls were more prominent in the delta than in the sigma band 74 , 75 .…”
Section: Discussionmentioning
confidence: 99%
“…Time spent in the behavioral stage of sleep is a crucial part of a child's development, and the neurophysiological activity captured with the sleep EEG can provide valuable insights into the child's brain connectivity. Previous research has shown a correlation between EEG patterns and behavioral and cognitive outcomes in healthy children ( Buchmann et al, 2011 ; Ednick et al, 2009 ; Reynaud et al, 2018 ) and infants ( Jaramillo et al, 2021 ; Schoch et al, 2021 ). The non-rapid-eye-movement (NREM) sleep EEG, and therein specifically the oscillatory activity of slow wave activity (SWA, spectral power in the 1–4.5 Hz frequency range), undergoes drastic changes across childhood and the period of brain development, for example, with a shift in the predominant location of SWA from posterior to anterior regions of the scalp ( Kurth et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…It also provides information on the amplitude, PSD, and spectrogram of any detected sleep spindle. It is anticipated that Deep-spindle would find widespread use in many therapeutic settings, therefore reducing time and labor-intensive manual annotation (Jaramillo et al, 2023). Because variations in spindle characteristics (such as density, frequency, shape, and spatial distribution) help identify a number of sleep disorders, including sleep apnea, insomnia, narcolepsy, restless leg syndrome, and parasomnias, sleep spindles are significant from a clinical standpoint.…”
Section: Introductionmentioning
confidence: 99%